Optimalisasi Kegiatan Bongkar Muat Container pada PT Pelindo Multi Terminal Branch Sibolga - Rizky Erwandy Sinaga; Suratni Ginting; Lilis Lilis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine how to optimize container loading and unloading activities at PT. Pelindo Multi Terminal Sibolga Branch. Container loading and unloading activities are one of the main activities in port operations that greatly affect the efficiency and productivity of maritime logistics. PT. Pelindo Multi Terminal Sibolga Branch as one of the port service providers has an important role in ensuring the flow of goods in the West Coast of North Sumatra. This study is to analyze and identify factors that affect container loading and unloading performance as well as optimization strategies to improve time, costs, and resource utilization. The methods used in this study include field observations, interviews with related parties, and analysis of historical data on operational activities. The results of the study indicate that the main obstacles come from limited equipment, lack of coordination between parties, and low utilization of information technology. Suggested optimization efforts include the addition of heavy equipment for unloading, increasing workforce training, and digitalizing monitoring and scheduling systems.